The Relationship Between Sanitation Of Premises And Equipment With The Presence Of Escherichia Coli Bacteria In Refillable Drinking Water Depots In The Working Area Of The Gemuruh Water Health Center - Fitria Eka Putri; Alfita Sari; Adelina Fitri; Fajrina Hidayati; Hubaybah Hubaybah (Lembaga Pengembangan Kinerja Dosen, 2023)
According to data from the Bungo District Health Service for 2021, the number of refill drinking water depots (DAMIU) has reached 283. In the working area of the Air Gemuruh Community Health Center there are 26 DAMIU that meet the requirements, 3 (11.5%) and those that do not meet the requirements there are 88.5%. The aim of this research is to determine the relationship between sanitation of premises and equipment and the presence of Escherichia Coli bacteria at the refill drinking water depot in the Air Gemuruh Health Center work area in 2023.This research is a quantitative type with a cross sectional design. Samples were taken using the total sampling method, totaling 35 DAMIU. Univariate and bivariate analysis used Fisher's test. This study found that it could not be concluded that sanitation of premises and equipment had a relationship with the presence of Escherichia Coli bacteria in the Air Gemuruh Health Center Working Area. It is concluded that the variables of sanitation of premises and equipment cannot be concluded that there is a relationship because the data produced is constant.